Isolated mechanism study on in situ CO2 EOR. (15th October 2019) - Wang, Shuoshi; Li, Keren; Chen, Changlong; Onyekachi, Ogbonnaya; Shiau, Benjamin; Harwell, Jeffrey H.
Highlights: IFT reduction between crude oil and hydrolyzed/unhydrolyzed urea solution was measured. The wettability alteration of in situ CO2 EOR was directly observed by contact angle measurement. The effectiveness of the proposed in situ CO2 EOR system was demonstrated in carbonate and sandstone reservoirs. The mechanism and the factors that affect the effectiveness of the in situ CO2 EOR system were quantified. The screening criteria for in situ CO2 EOR candidates are proposed. Abstract: In situ CO2 enhanced oil recovery (ICE) has great potential for the mature oil field. ICE can deliver CO2 to the targeted formation by the injection of CO2 producing agents which decompose in the reservoir to release CO2 and other oil recovery enhancing compounds. The mechanism of the ICE system was evaluated experimentally. Alkali and hydrotrope induced interfacial tension (IFT) reduction were studied with crude oils that have different acid numbers and also dodecane. The independent and combined effect of the ICE system on wettability reversal was quantified by contact angle measurement with different fluid systems and lithology. Ten one-dimensional sand pack flooding tests with different lithology and fluid systems were designed to isolate the different recovery mechanisms and study their individual contribution to the final tertiary recovery. From the experimental results, the highest IFT reduction by alkali effect was from 21 mN/m to 0.77 mN/m. The wettability of clean sandstone and sandstone aged in crude oil were responsive to different concentrations of NH3 solution. The sandstone surface became more water-wet with increase in NH3 (aq) concentration. The wettability of carbonate core samples were not strongly affected by the NH3 solution. Both aged sandstone and carbonate core samples showed significant wettability reversal from oil-wet to water-wet after the ICE treatment. After a series of sand pack flooding tests, it was shown that the effect of CO2 was more dominant in carbonate reservoirs and NH3 (aq) contribution to the tertiary recovery increased with the increase of the crude oil acid number. The results help elucidate the mechanisms in ICE and their contribution to the final oil recovery.